2007
DOI: 10.1093/hmg/ddm293
|View full text |Cite
|
Sign up to set email alerts
|

An antisense transcript spanning the CGG repeat region of FMR1 is upregulated in premutation carriers but silenced in full mutation individuals

Abstract: Expansion of the polymorphic CGG repeats within the 5'-UTR of the FMR1 gene is associated with variable transcriptional regulation of FMR1. Here we report a novel gene, ASFMR1, overlapping the CGG repeat region of FMR1 and transcribed in the antisense orientation. The ASFMR1 transcript is spliced, polyadenylated and exported to the cytoplasm. Similar to FMR1, ASFMR1 is upregulated in individuals with premutation alleles and is not expressed from full mutation alleles. Moreover, it exhibits premutation-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
262
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 237 publications
(269 citation statements)
references
References 53 publications
6
262
1
Order By: Relevance
“…The ASFMR1 gene promoter is located within intron 2 of the FMR1 gene. 21 Interestingly, the expression of ASFMR1, similar to that of FMR1, is elevated in fragile X premutation carriers and decreased in individuals with full mutation alleles. 21 To date, translation of the ASFMR1 gene has not been reported, and whether it has a pathogenic role is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The ASFMR1 gene promoter is located within intron 2 of the FMR1 gene. 21 Interestingly, the expression of ASFMR1, similar to that of FMR1, is elevated in fragile X premutation carriers and decreased in individuals with full mutation alleles. 21 To date, translation of the ASFMR1 gene has not been reported, and whether it has a pathogenic role is not known.…”
Section: Discussionmentioning
confidence: 99%
“…A second model, "RAN translation", represents noncanonical translation that results in expression of toxic polyglycine-and polyalanine-containing products (128,129). A third model, "antisense FMR1 (ASFMR1) toxicity", involves the expression of antisense transcripts products (130). Mitochondrial abnormalities have also been found in FXS and premutation carriers.…”
Section: Premutation Genotypesmentioning
confidence: 99%
“…CTCF (CCCTC-binding factor), the first insulator protein found in mammals, is among the nuclear proteins binding the methylation boundary. CTCF also binds to the promoter and intron 2 of the FMR1 gene [Ladd et al, 2007]. We recently investigated the role of CTCF on FMR1 transcription and observed that CTCF depletion did not cause spreading of methylation over the FMR1 promoter of UFM cell lines, in spite of the presence of the CGG expansion in the full mutation range [Lanni et al, 2013].…”
Section: Fragile X Syndromementioning
confidence: 99%
“…These can be generated by processing longer double-stranded RNAs formed by complementary pairing of mRNAs and long antisense transcripts due to bidirectional transcription at the same locus [Morris, 2009]. The presence of long ncRNAs overlapping (at least in part) critical mRNAs has been proven in several imprinted loci such as those of Angelman and Beckwith-Wiedemann syndromes [Rougeulle et al, 1998;Lee et al, 1999] as well as those of Fragile X [Ladd et al, 2007;Chen et al, 2008;De Biase et al, 2009]. It is assumed that double-stranded RNAs are processed by the RNAi machinery into siRNAs that induce either degradation of complementary mRNAs (post-transcriptional gene silencing) or cause RNA-mediated DNA methylation (transcriptional gene silencing).…”
Section: Rna Transcriptsmentioning
confidence: 99%
See 1 more Smart Citation